2021
DOI: 10.3390/su13147946
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Perceived Value and Purchase Intention toward Eco-Friendly Athleisure Apparel: Insights from U.S. Millennials

Abstract: Given the recent trend of the athleisure lifestyle in the U.S., this study sought to examine female millennial consumers’ value perceptions for purchasing recycled polyester-made athleisure apparel. Using an inductive approach with grounded theory, the perceived green value (PGV) framework was applied to guide data collection through the in-depth interviews and data analysis. The findings of the study provide theoretical insights and sustainable solutions for the industry and academia. Five main values identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 24 publications
1
26
0
3
Order By: Relevance
“…Researchers also found that consumer perceived value is a key organism factor bridging the environmental stimuli and consumers' responses [36,50,51]. Consumer perceived value (both hedonic and utilitarian value) along with perceived risk and perceived behavioral control (PBC) were repeatedly reported as the significant factors influencing consumers' adoption behaviors toward new technologies or new shopping channels [52][53][54].…”
Section: S-o-r Modelmentioning
confidence: 99%
“…Researchers also found that consumer perceived value is a key organism factor bridging the environmental stimuli and consumers' responses [36,50,51]. Consumer perceived value (both hedonic and utilitarian value) along with perceived risk and perceived behavioral control (PBC) were repeatedly reported as the significant factors influencing consumers' adoption behaviors toward new technologies or new shopping channels [52][53][54].…”
Section: S-o-r Modelmentioning
confidence: 99%
“…It would therefore be important to consider to what extent the results of this Italian study differ from those obtainable in other countries. Moreover, future studies might integrate in the present theoretical model consumers' values related to the attributes of sustainable fashion, such as functional, social, and emotional values [110].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Previous research has indicated that rental apparel models are more sustainable than traditional consumption models [15][16][17]. The reasons for this greater sustainability include being able to extend the life of products through use intensification and item repair; designing more durable products that last longer to avoid creating unnecessary waste; the need to create fewer products that satisfy more people, which reduces resource, water, electricity, and material consumption; the opportunity to reduce water and energy usage while better preserving garments through more professional cleaning services and technologies utilized by clothing rental companies; and helping consumers reduce overconsumption [18][19][20]. Even though renting apparel can provide all of these environmental benefits, it is not a guarantee that apparel rental companies will achieve all of these sustainable practices or publicly orient themselves as sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2, 3,4,5,6,7,8,9,10,11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28,30,31,32,33,34,35,37,38,39,40,41,42,43,44,45,46,47,48,49…”
mentioning
confidence: 99%